The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1021/acs.jpcc.5b00282
|View full text |Cite
|
Sign up to set email alerts
|

Study of ZnSnO3-Nanowire Piezophotocatalyst Using Two-Step Hydrothermal Synthesis

Abstract: This paper presents the report on the piezophotocatalysis of single-crystal rhombohedral ZnSnO 3 nanowires. An essential feature of this study was the close coupling of the functions of piezophototronics (semiconductors, piezoelectricity, and photonics) and photocatalysis for achieving synergistic catalytic performance. Vertically aligned lead-free noncentrosymmetric high purity ZnSnO 3 nanowires (LiNbO 3 -type, R3c) were fabricated using a two-step hydrothermal reaction. The piezophototronic effect was demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 60 publications
5
64
1
Order By: Relevance
“…Thus, various hydrothermal reaction approaches were applied in the present research to fabricate ZTO nanowire arrays for (1) enabling the easy distinguishability of LN‐type ZTO phases from the supporting substrate; (2) growing considerably well‐aligned ZTO nanowires along the substrate normal; (3) further enhancing the piezotronic and piezophototronic effects; and (4) attaining synergistic piezophotocatalysis through ultrasonic vibration combined with a piece of transparent glass. The results revealed an excellent piezophototronic effect approximately two times higher than that reported previously . In addition, the corresponding Schottky barrier modulation under various applied stresses was quantitatively verified.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…Thus, various hydrothermal reaction approaches were applied in the present research to fabricate ZTO nanowire arrays for (1) enabling the easy distinguishability of LN‐type ZTO phases from the supporting substrate; (2) growing considerably well‐aligned ZTO nanowires along the substrate normal; (3) further enhancing the piezotronic and piezophototronic effects; and (4) attaining synergistic piezophotocatalysis through ultrasonic vibration combined with a piece of transparent glass. The results revealed an excellent piezophototronic effect approximately two times higher than that reported previously . In addition, the corresponding Schottky barrier modulation under various applied stresses was quantitatively verified.…”
Section: Introductionsupporting
confidence: 58%
“…On the basis of our previous research, ITO/glass, instead of FTO/glass, was investigated. Furthermore, varying the hydrothermal reaction time for Steps 1 and 2 was found to produce substantially different results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[17,28] In addition, it is an efficient strategy to either create or increase polarization by controlling the degree of phase transformation from non-ferroelectrics to ferroelectrics by thermal treatment. [20,23] Fourthly,t he development of new types of polarization, such as pyroelectric polarization, magnetoelectric polarization, etc. Electric polarization is well known for enhancing the polarization of ferroelectric photoelectrodes (films), [31] but external polarization for powdery ferroelectric photocatalysts remain underexplored, and requires suitable polarization equipment with high voltages.For stress-induced piezoelectric polarization, more clean energy,s uch as wind, tide,m ovement, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Chang et al demonstrated that the photonexcitation and strain derived from mechanical bending largely increase the local conductance and effectively reduce the barrier height by producing ap ositive piezopotential, rendering enhanced charge carrier transfer. [23] Theenhancement was ascribed to the reduced recombination of photoinduced e À and h + and reinforced mobility of these charge carriers resulting from the energy band distortion caused by stress-induced piezoelectric polarization. [22] Lo et al prepared vertically aligned ZnSnO 3 nanowires on FTO glass,a nd demonstrated ah igher UV photocatalytic activity for MB degradation under stress than that without applied stress ( Figure 4c).…”
Section: Piezoelectric Polarization Promoted Bulk Charge Separationmentioning
confidence: 99%